International Corporate Governance After Sarbanes‐Oxley 2012
DOI: 10.1002/9781119201885.ch3
|View full text |Cite
|
Sign up to set email alerts
|

Governance and Performance Revisited

Abstract: Using rich and accurate data from Oslo Stock Exchange firms, we find that corporate governance matters for economic performance, insider ownership matters the most, outside ownership concentration destroys market value, direct ownership is superior to indirect, and that performance decreases with increasing board size, leverage, dividend payout, and the fraction of non-voting shares. These results persist across a wide range of single-equation models, suggesting that governance mechanisms are independent and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 64 publications
2
13
0
2
Order By: Relevance
“…For example, La Porta et al (1999) found that ownership is concentrated about 10 per cent in the UK and 20 per cent in the US. Beiner et al (2004) found the ownership concentration for Swiss listed firms to be about 12 per cent, and Bohren and Odegaard (2003) documented the ownership concentration to be about 29 per cent, while the ownership concentration in developing countries is quite high. 10 La Porta et al (1999) US and UK 3 10% for USA 20% for UK 9…”
Section: Table 4: Descriptive Analysis For All Variablesmentioning
confidence: 99%
“…For example, La Porta et al (1999) found that ownership is concentrated about 10 per cent in the UK and 20 per cent in the US. Beiner et al (2004) found the ownership concentration for Swiss listed firms to be about 12 per cent, and Bohren and Odegaard (2003) documented the ownership concentration to be about 29 per cent, while the ownership concentration in developing countries is quite high. 10 La Porta et al (1999) US and UK 3 10% for USA 20% for UK 9…”
Section: Table 4: Descriptive Analysis For All Variablesmentioning
confidence: 99%
“…Panel (a) shows that the average direct (personal) ownership is about 50% in a PCC bank and 20% in a commercial bank. The corresponding figure in Norwegian non-banks is 18% during a similar period (Bøhren and Ødegaard, 2006). This high incidence of direct ownership in our sample firms suggests that being ownerless is more of a governance handicap in banking than in other industries.…”
Section: Restrictions On Ownershipmentioning
confidence: 52%
“…The opposite impression is given by panel (b), which shows that ownership concentration in banks is considerably below the typical ownership level in Norwegian industry, which is about 30% for the largest owner and 55% for the five largest owners as a group (Bøhren and Ødegaard, 2006). The low ownership concentration in banking is due to regulation, which mandates permission from the Ministry of Finance for any investor or coalition of investors to own more than 10% of a bank's stock.…”
Section: Restrictions On Ownershipmentioning
confidence: 90%
“…Fundamentação Teórica Fórmula Fonte DCONT Bohren & Odegaard (2004), Lameira (2007), Ehikioya (2009), Peixoto (2012 Para representar os mecanismos de governança corporativa utilizaram-se as seguintes variáveis, fundamentadas na literatura sobre o tema: direito de controle (DCONT), direito sobre o fluxo de caixa (DSFC), separação entre presidente do conselho de administração e o CEO (SEP_PCEO), grau de independência do conselho de administração (GICA), índice de payout (PAYOUT), direito de voto das ações preferenciais (DV_AP), emissão de ADRs (ADR), prioridade no reembolso do capital em caso de liquidação (PRC), remuneração total dos administradores (REM_TOT), participação dos administradores nos resultados da empresa (PART_RES), plano de opções para executivos (STK_OP) e auditoria global (AUD_GLOB Todos os índices de governança apresentaram distribuição normal, de acordo com o teste de Kolmogorov-Smirnov (valor de p > 0,01). O maior índice foi o IGC12 com média de 0,50 e o menor índice foi o IGCN, com média de 0,42.…”
Section: Variáveisunclassified